Exploring the complementarity between foreign technology, embedded technology and increase of productive capacity - González-Blanco, Jennifer; Vila-Alonso, Mercedes; Guisado-González, Manuel (Technological and Economic Development of Economy, 2019)
This study analyzes the complementarity of foreign technology acquired under license agreements, technology embedded in machinery and equipment and increase in a company’s productive capacity. We use panel data on Brazilian manufacturing companies from the World Bank Surveys. We used the random effects models, estimated by maximum likelihood. The results indicate that foreign technology, embedded technology and increase of productive capacity have a positive and significant impact on labor productivity. The complementarity test reveals that the relationship between the two technologies analyzed is conditionally substitutive and that the relationship between each of these technologies and increase of productive capacity is conditionally complementary.